Implementasi Sistem Monitoring Kualitas Air Akuarium Menggunakan ESP32, Sensor pH, dan Sensor Turbidity - Fadli Habib Rizieq; Ardelia Astriany Rizky; Jajat Sudrajat (POLITEKNIK PIKSI GANESHA, 2026)
This research aims to design a tool and implement an aquarium water quality monitoring system using an ESP32 microcontroller connected to a pH sensor and a turbidity sensor. This system is capable of monitoring pH values ​​and water clarity levels through real-time input data from the turbidity sensor, and displays the data on an LCD screen. A buzzer will sound as an alarm if the turbidity level exceeds a predetermined limit. Test results show that the system functions stably and provides accurate results in identifying changes in water parameters. It is hoped that this system can be an efficient and cost-effective solution for fish hobbyists in maintaining aquarium water quality. Keywords: pH sensor, turbidity, water monitoring